2013
DOI: 10.1007/s11096-013-9806-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of pharmaceutical care service on hospitalized patients with chronic kidney disease in Jordan

Abstract: The current study indicated that hospitalized patients with CKD suffer from multiple TRPs mostly related to efficacy of medications and patients monitoring. Clinical pharmacists substantially contributed towards the care of hospitalized CKD patients through optimizing progression modifying therapies, medications safety and management of CKD complications. Based on this study it is strongly recommended to implement pharmaceutical care services for hospitalized CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…The normalization of eGFR had an impact on drug dosing decisions; there was a higher level of agreement among the equations when the normalization to BSA was removed from the eGFR values. This aligns with the National Kidney Disease Education Program's suggested approach that either an eCrCl or an eGFR with BSA normalization removed is acceptable for drug dosing estimations …”
Section: Discussionsupporting
confidence: 53%
“…The normalization of eGFR had an impact on drug dosing decisions; there was a higher level of agreement among the equations when the normalization to BSA was removed from the eGFR values. This aligns with the National Kidney Disease Education Program's suggested approach that either an eCrCl or an eGFR with BSA normalization removed is acceptable for drug dosing estimations …”
Section: Discussionsupporting
confidence: 53%
“…Many studies reported pharmacists’ interventions in: modifying drug doses and recommending new pharmacotherapy; [ 16 , 19 , 21 – 23 , 25 – 27 , 29 , 30 , 32 – 40 , 52 , 59 ]; interacting with a member of the multidisciplinary team; [ 15 – 17 , 19 – 21 , 23 – 25 , 27 , 31 , 32 , 34 – 38 , 40 – 43 ] requesting and monitoring laboratory parameters; [ 15 , 23 , 25 , 27 , 33 , 34 , 36 , 37 , 43 ] assessing appropriateness of medications prescribed for hospitalised patients at each point of care; [ 17 , 22 , 29 , 30 , 35 – 38 , 40 , 57 ]. Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation. [ 37 , 43 ] Development of protocols and compiling and updating guidelines were also described in two studies [ 22 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation. [ 37 , 43 ] Development of protocols and compiling and updating guidelines were also described in two studies [ 22 , 34 ]. Performing medication reconciliation [ 46 ]; providing patient medication counselling, education on disease status or medication, conducting motivational interviews to improve adherence were also reported [ 15 , 25 , 27 , 29 , 30 , 34 , 36 , 37 , 42 , 43 , 47 – 50 , 55 , 57 , 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the recent recognition of the benefits of PCSs, its implementation in patient care settings to achieve quality service remains a challenge. 5 , 6 , 12 , 22 – 24 Knowing that one of the major stakeholders of PCSs is the patient, patients’ awareness and demands of the service should be reflected to develop such services.…”
Section: Discussionmentioning
confidence: 99%